Head Posture and Functional Ability of Upper Extremity in Adolescents Use Smartphone (Medico Legal Update, 2020)
Objective: This study aimed to determine the impact of smartphone use in head posture and functionalability of upper extremity in adolescents and the correlation between them.Design: Cross sectional design.Method: Forty adolescents divided into two groups (group I and group II) based on the smartphonetime use per day. They were assessed for neck pain by Visual analogue scale (VAS), the disability of theupper extremity by Upper Extremity Functional Index (UEFI) and the head posture angles by AutoCADphotographic analysis.Results: The results of this study represented significant differences in all measurable variablesinthe group(II) as compared to the group (I). Also, the results of this study represent there were significant strongrelationships between the measurable variables.Conclusion: We could conclude that the prolonged duration of smartphone use had significant effects on thehead posture and functional ability of adolescents.